Peran Pemerintah Dalam Pelaksanaan Ibadah Haji Di Bali - Santika R. Hasan; Sindri Potalangi; Affan Naufal Afdali; Andi Mardiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the context of the Hajj pilgrimage in Bali, the government's role takes center stage. The background involves a surge in the number of pilgrims wishing to perform Hajj, juxtaposed with limited facilities and supporting infrastructure in the region. The research problem revolves around assessing the effectiveness of the government's initiatives in facilitating and regulating the Hajj pilgrimage in Bali, encompassing regulatory measures, accommodation infrastructure, and pilgrim management. The evaluation of the government's role reveals that their efforts have enhanced the quality of services and comfort for Hajj pilgrims, although challenges persist regarding capacity and logistical management. In conclusion, the government's role is pivotal in ensuring the success of the Hajj pilgrimage in Bali by improving infrastructure, enacting appropriate regulations, and enhancing inter-agency coordination. The novelty of this work lies in its in-depth analysis of the government's concrete measures to enhance the quality of the Hajj pilgrimage in Bali, along with providing constructive recommendations for future improvements.